Knowledge, Attitudes, and Preventive Behaviors Towards Stroke: A Study Among Employees of PT. PP London Sumatra Indonesia Tbk. Palembang Branch - Fatimah Khairunnisa Lubis; Pinto Desti Ramadhoni; Rini Nindela (Sriwijaya Journal of Medicine, 2022)
A stroke occurs when a blood vessel that carries oxygen and nutrients to the brain is either blocked or ruptured. If the blood supply to part of the brain is interrupted or stopped, this can cause brain cells to die. Stroke is a health problem that must be noticed and understood by the whole community considering the high mortality and disability rates among working-age adults caused by this disease. Limited public knowledge towards stroke will result in no/lack of prevention efforts and can lead to delays in treating stroke. This research is a descriptive study with a cross-sectional approach that aims to describe the knowledge, attitudes, and preventive behaviors towards stroke among employees of PT. PP London Sumatra Indonesia Tbk. Palembang Branch. The primary source for the data used was an online questionnaire addressed to 48 employees of PT. PP London Sumatra Indonesia Tbk. Palembang Branch as the study subjects. Based on the results of measuring the variables, it can be concluded that most of the employees of PT. PP London Sumatra Indonesia Tbk. Palembang Branch have poor knowledge, good attitudes, and poor preventive behaviors towards stroke.